2019
DOI: 10.1002/ca.23467
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Dense and Sparse Areas in the Longitudinal Smooth Muscle of the Anal Canal: Anatomical and Histological Analyses Inspired by Magnetic Resonance Images

Abstract: Magnetic resonance images of the anal canal show small, circular, low-intensity areas arranged in a row and a high-intensity area surrounding them internally and externally in the longitudinal muscle layer that cannot be explained by current anatomical findings. The purpose of this study was to elucidate the detailed structure of the longitudinal smooth muscle of the anal canal and to interpret the magnetic resonance image of the longitudinal muscle. Specimens for macroscopic anatomy and histology were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Anti‐smooth actin (ready‐to‐use Actin, Smooth Muscle Ab‐1, Clone 1A4; Thermo Fisher Scientific, Fremont, CA) and anti‐skeletal myosin (ready‐to‐use Myosin, Skeletal Muscle Ab‐2, Clone MYSN02; Thermo Fisher Scientific) were used for immunological staining to confirm the distributions of smooth and skeletal muscle fibers. The detailed procedures have been described in previous reports (Muro et al, 2014; Muro et al, 2018; Muro et al, 2019; Muro et al, 2020; Nakajima et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anti‐smooth actin (ready‐to‐use Actin, Smooth Muscle Ab‐1, Clone 1A4; Thermo Fisher Scientific, Fremont, CA) and anti‐skeletal myosin (ready‐to‐use Myosin, Skeletal Muscle Ab‐2, Clone MYSN02; Thermo Fisher Scientific) were used for immunological staining to confirm the distributions of smooth and skeletal muscle fibers. The detailed procedures have been described in previous reports (Muro et al, 2014; Muro et al, 2018; Muro et al, 2019; Muro et al, 2020; Nakajima et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The anatomy around the rectum and anal canal has attracted increased attention since the development of anorectal surgery (Aigner et al, 2004; Kraima et al, 2016, Tsukada et al, 2016; Nakajima et al, 2017; Muro, Tsukada, Harada, Ito, & Akita, 2018; Muro, Tsukada, Harada, Ito, & Akita, 2019; Okada et al, 2019). We previously analyzed the muscle structure around the rectum and anal canal anatomically (Baramee, Muro, Suriyut, Harada, & Akita, 2020; Kato, Muro, Kato, Miyasaka, & Akita, 2020; Muro et al, 2014; Muro et al, 2018; Muro et al, 2019; Muro et al, 2020; Nakajima et al, 2017; Suriyut, Muro, Baramee, Harada, & Akita, 2020; Tsukada et al, 2016). Those studies revealed a very interesting distribution of smooth muscle in this region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-smooth actin (ready-to-use actin, smooth muscle Ab-1, clone 1A4; Thermo Fisher Scientific, Fremont, CA) and anti-skeletal myosin (ready-to-use myosin, skeletal muscle Ab-2, clone MYSN02; Thermo Fisher Scientific) were used for immunological staining to confirm the distribution of smooth and striated muscle fibers. The detailed procedures have been described previously 11,13,[15][16][17]20 .…”
Section: Histologymentioning
confidence: 99%
“…We have reported the characteristic structure of the pelvic floor, in which the striated muscles share their muscle bundles and are continuous, and the smooth muscle occupies the space between them [11][12][13][14][15][16][17][18][19][20] . These studies suggest that striated and smooth muscles coordinate in anal function and pelvic floor support.…”
mentioning
confidence: 99%